RULES-BASED ACCOUNTING STANDARDS AND SEC ENFORCEMENT - Baranek, Devon (Journal of Accounting, Business and Management (JABM), 2020)
This archival study investigates the association between rules-based violations and the likelihood of SEC enforcement.  I utilize two samples of firms subject to SEC investigations: 1) firms with investigations that end in an enforcement action and 2) firms with investigations that are dropped, and examine the impact of rules-based accounting violations on enforcement.  Each enforcement action in the sample specifically cites the GAAP standard violated, and the degree to which the standards contain rules-based characteristics is quantified.  The violations are classified as either rules-based or principles-based and a multivariate analysis is performed.  The ?roadmap? theory suggests that firms who commit rules-based violations are more likely to be subject to SEC enforcement, while the ?roadblock? theory predicts the opposite effect.    Overall, the results suggest the SEC is less likely to litigate cases that involve rules-based accounting violations, or more likely to drop/dismiss investigations centered on rules-based violations, consistent with the ?roadblock? theory.  No evidence is found of a relation between rules-based accounting violations and the dollar magnitude of penalties assessed.  These results are relevant for financial statement preparers, auditors, and regulators.